Trauma cultural y memoria histórica en El deber de Fenster de Humberto Dorado y Matías Maldonado - Garavito, Lucía (Latin American Theatre Review, 2016)
How should theatrical activity in Colombia acknowledge the country’s violent political life and the thousands of victims of an armed conflict that has lasted for almost six decades? What role should theatre play in the context of human-rights violations and institutional (in)justice to configure a collective memory and history? This study focuses on El deber de Fenster, a documentary drama by Humberto Dorado and Matías Maldonado, as an agent of cultural trauma. The dramaturgical dimension of the massacre of Trujillo as embodied in Daniel Arcila’s manuscript and story implies both an exploration of the brutal practices that fragment the national body and a (re)membering of individuals and events in an effort to collectively mourn victims and symbolically reconstruct the torn social fabric.